До моделювання стохастичних ситуацій ухвалення рішень - Ivanenko, V. І.; Mikhalevich, V. M. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2010)
The definitions of lottery and matrix models of the decision making situation with a stochastic cause-effect mechanism are given. It is shown that these models are equivalent for the simulation of broad class of such situations.